Laparoscopy-assisted ERCP (LA-ERCP) following bariatric gastric bypass surgery: initial experience of a single UK centre. Issue 1 (14th May 2015) - Paranandi, Bharat; Joshi, Deepak; Mohammadi, Borzoueh; Jenkinson, Andrew; Adamo, Marco; Read, Samantha; Johnson, Gavin J; Chapman, Michael H; Pereira, Stephen P; Webster, George J
Abstract : Background: Bariatric gastric bypass surgery is being increasingly performed, but endoscopic retrograde cholangiopancreatography (ERCP) in these patients poses a unique challenge because of a lack of per-oral access to the stomach. Small series suggest a higher technical success rate using laparoscopy-assisted ERCP (LA-ERCP) than with an enteroscopic approach via the Roux-en-Y anastomosis. We present initial experience of LA-ERCP in our unit. Design: Retrospective case series of consecutive patients undergoing LA-ERCP in our unit between September 2011 and July 2014. Data was retrieved from electronic, clinical and endoscopy records. Results: Seven LA-ERCPs were performed. All seven patients were female, with median age 44 years (range 36–71). Indications included symptomatic bile duct stones (5/7), benign papillary fibrosis (1/7) and retained biliary stent (1/7). 5/7 (71%) patients had had a prior cholecystectomy. To facilitate LA-ERCP, laparoscopic gastrostomy ports were created in all patients. Duodenal access, biliary cannulation and completion of therapeutic aim were achieved in all patients. 6/7 (86%) patients required endoscopic sphincterotomy. The median duration of procedures was 94 min (range 70–135). Median postoperative length of stay was 2 days (range 1–9). One patient developed mild postprocedural acute pancreatitis, and another patient developed a mild port-site infection. Otherwise, no procedure-related complications were seen. All patients remained well on follow-up (median 14 months (range 1–35) from date of ERCP), with no evidence of further biliary symptoms. Conclusions: Our early experience of LA-ERCP is that it is safe and effective. The technique may require particular consideration, as bariatric surgery is increasingly performed, in a patient group at significant risk of bile duct stones.